Pemanfaatan Podcast Edukasi sebagai Media Alternatif dalam Meningkatkan Literasi Membaca Siswa SD - Jusman Jusman (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Reading literacy is one of the basic skills that must be mastered by elementary school students to support their academic success. However, low interest in reading and the lack of interesting learning media are challenges in improving reading literacy. One of the media that can be utilized is educational podcasts, which offer interactive and flexible audio-based learning experiences. This literature study aims to analyze the effectiveness of educational podcasts as an alternative media in improving elementary school students' reading literacy. The results of the study show that the use of podcasts in learning can improve reading comprehension, listening skills, and enrich students' vocabulary. In addition, podcasts also provide a more enjoyable learning experience than conventional methods. This study recommends the integration of podcasts into the curriculum and training for teachers to optimize their use in learning. Thus, educational podcasts have the potential to be innovative media that support the improvement of elementary school students' reading literacy effectively